Terrorizing police: revisiting ‘the policing of terrorism’ from the perspective of Danish police detectives - Sausdal, David (European journal of criminology, 2021)
A common conclusion in criminology is that fears of terrorism are being (mis)used. The media have used them to market their products, politicians to promote themselves as protectors, and the police have profited through being granted increased powers and resources. Some scholars even argue that one outcome has been a growing militarization of the police. This article revisits this debate. It does so by taking an ethnographic look at how the war on terror has affected a number of Danish police detectives’ daily work. In doing so, the paper shows how the idea that police (mostly) benefit from the war on terror somewhat misses the mark – at least when seen from the perspective of frontline officers. As the article demonstrates, rather than mobilizing Danish detectives, terrorism most often makes them feel mired.